2020
DOI: 10.1002/ecs2.3053
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation cascades create a predation refuge for biodiversity in a novel connected habitat

Abstract: Communities structured via facilitation cascades whereby one habitat-forming species promotes a secondary habitat-forming species with synergistic effects on biodiversity are increasingly documented. Habitat-formers can also extend the realized niche of other habitat-forming species by facilitating their recruitment into novel environments across heterogeneous landscapes. However, further understanding of whether secondary habitat-formers in these novel environments differ in their structure or support differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 75 publications
1
5
1
Order By: Relevance
“…Algae have frequently been shown to provide protection to epifauna against predation Bueno et al, 2020;Lanham et al, 2020;Ware et al, 2019), but in this system, we found no evidence of direct top-down control of epifaunal numbers by predators. On the contrary, we did find evidence of both top-down (grazing) and bottom-up (nutrient supply) effects on macroalgae, which had indirect effects on epifauna by modifying their habitat.…”
Section: Discussioncontrasting
confidence: 86%
“…Algae have frequently been shown to provide protection to epifauna against predation Bueno et al, 2020;Lanham et al, 2020;Ware et al, 2019), but in this system, we found no evidence of direct top-down control of epifaunal numbers by predators. On the contrary, we did find evidence of both top-down (grazing) and bottom-up (nutrient supply) effects on macroalgae, which had indirect effects on epifauna by modifying their habitat.…”
Section: Discussioncontrasting
confidence: 86%
“…There is also some evidence that habitat-forming species can facilitate other spatially distant habitat-formers, that is, facilitation often occurs at larger, seascape scales (Gribben et al, 2019). For example, in soft-sediment environments, beds of mussels can promote the high abundances of other bivalves by altering hydrodynamic regimes at distances of 100s of meters away from the mussel beds (Donadi et al, 2013), and clams provide a hard substratum for fucoid settlement thus extending their distribution from their natal habitat (rocky shore) to a connected novel habitat (Lanham et al, 2020). Therefore, kelp restoration may only succeed if the habitat is made more amenable for growth by the presence of another habitat-forming species (e.g., another kelp species) in the local seascape.…”
Section: Synergies In Kelp Forest Restoration Intraspecific Facilitat...mentioning
confidence: 99%
“…To test if differences in predator communities among habitat‐settings explained differences in macroinvertebrate communities, we quantified predators in each habitat‐setting using un‐baited remote underwater video cameras (Lanham et al 2020; Martínez‐Baena et al 2022). During the first experiment, the reef units were filmed twice over 2 days in May–June 2021.…”
Section: Methodsmentioning
confidence: 99%